Rehabilitation of the habitat of modern cities in Syria - A. Aasem; V. N. Tkachev (Vestnik MGSU)
Introduction. Cities of Syria have a dual structure of building organization: a traditional carpet-built dwelling with a conservative lifestyle of the inhabitants and the “European city” that developed during the periods of colonization — each of which focuses on a separate rehabilitation method. The subject of the study is the restoration of the destroyed cities of Syria. The aim is to present the hypothesis of updating the rehabilitation paradigm, integrating the methodology of urbanism and volumetric construction by introducing programmes for the fractal distribution of patterns of urban life support.Materials and methods. To form the prerequisites for the reconstruction of the “background” development and the “European city”, the established socio-ethnic parameters of the inhabitants of Syrian cities of different historical morphogenesis, the typology of housing were studied using available literary sources and natural objects. The background building is accepted as the basic object of restoration work based on the simplest universal system of fractal distribution of life support patterns. An explanation of the essence of this system, which temporarily replaces the standard methods and sequence of urban reconstruction, is given.Results. The models of “carpet” building reconstruction and the specifics of the conceptual approach to the use of architecture as a means of preventing migration, preserving the national identity of the image of the city are described.Conclusions. There are concerns about the fate of Syrian cities, the destruction of which threatens to disintegrate the culture of this ancient country, the salvation of which largely depends on a competent architectural strategy for restoring the habitat.